The utility of two-dimensional shear wave elastography for predicting prostate cancer: a preliminary study - Jeon, Seong Soo; Kim, Chan Kyo; Park, Sung Yoon; Chung, Jae Hoon; Kang, Minyong; Sung, Hyun Hwan; Jeong, Byong Chang (Ultrasonography, 2023)
Purpose: This study investigated whether two-dimensional shear wave elastography (2D-SWE), using a newly developed device, is useful for predicting prostate cancer (PCa).Methods: In this prospective study, 38 patients with suspected PCa underwent 2D-SWE, followed by a standard systematic 12-core biopsy with and without a targeted biopsy. Tissue stiffness on SWE was measured in the target lesion and in 12 regions of the systematic biopsies, and the maximum (Emax), mean (Emean), and minimum (Emin) values of stiffness were generated. The area under the receiver operating characteristic curve (AUROC) for predicting clinically significant cancer (CSC) was calculated. Interobserver reliability and variability were evaluated using the intraclass correlation coefficient (ICC) and Bland-Altman plots, respectively.Results: PCa was found in 78 of 488 regions (16%) in 17 patients. In region-based and patientbased analyses, the Emax, Emean, and Emin values of PCa were significantly higher than those of benign prostate tissue (P<0.001). For the prediction of CSC, the AUROCs of Emax, Emean, and Emin in the patient-based analysis were 0.865, 0.855, and 0.828, while that of prostate-specific antigen density was 0.749. In the region-based analysis, the AUROCs of Emax, Emean, and Emin values were 0.772, 0.776, and 0.727, respectively. The interobserver reliability for the SWE parameters was moderate to good (ICC, 0.542 to 0.769), and the mean percentage differences on Bland-Altman plots were less than 7.0%.Conclusion: The 2D-SWE method appears to be a reproducible and useful tool for the prediction of PCa. A larger study is warranted for further validation.